2012
DOI: 10.1186/1478-4505-10-24
|View full text |Cite
|
Sign up to set email alerts
|

A review of the health and economic implications of patent protection, with a specific focus on Thailand

Abstract: BackgroundAlthough it has been two decades since the Thai Patent Act was amended to comply with the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS), there has been little emphasis given to assessing the implications of this amendment. The purpose of this review is to summarize the health and economic impact of patent protection, with a focus on the experience of Thailand.MethodsA review of national and international empirical evidence on the health and economic implications of patent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Much of the evidence linking patent prices and access to medicines have been highlighted in the case of HIV/AIDS (Borrell, , p. 505; The International Intellectual Property Institute, , p. 9; WHO, 2014, p. 26) . For instance, the result of a comparative study of patented and generic price differences of HIV/AIDS medicines in Thailand from 2001 to 2004 found that the patented drugs were 1.5–3 times more expensive than the equivalent generic version in 2001 (Yamabhai & Smith, , p. 14) . In another example, the price of an important ARV HIV drug, 3TC (Lamivudine and Epivir), was marketed and sold by Glaxo in the United States for US$3,271 while the generic version was sold for $190 and $98 by Cipla Ltd and Hetero Drugs Limited respectively (Oh, ).…”
Section: Part Ii: Patents the Trips Agreement And Access To Essentimentioning
confidence: 99%
“…Much of the evidence linking patent prices and access to medicines have been highlighted in the case of HIV/AIDS (Borrell, , p. 505; The International Intellectual Property Institute, , p. 9; WHO, 2014, p. 26) . For instance, the result of a comparative study of patented and generic price differences of HIV/AIDS medicines in Thailand from 2001 to 2004 found that the patented drugs were 1.5–3 times more expensive than the equivalent generic version in 2001 (Yamabhai & Smith, , p. 14) . In another example, the price of an important ARV HIV drug, 3TC (Lamivudine and Epivir), was marketed and sold by Glaxo in the United States for US$3,271 while the generic version was sold for $190 and $98 by Cipla Ltd and Hetero Drugs Limited respectively (Oh, ).…”
Section: Part Ii: Patents the Trips Agreement And Access To Essentimentioning
confidence: 99%
“…10,15 Counter arguments to this point are simple: if LMICs save money on medication expense, then these savings can be invested in improvement of their own drug manufacturing capacity and health systems. In Thailand, a study found that if relevant HIV/AIDs drugs were not patented, an additional 10,000 prescriptions could be made, which would increase access by 50%.…”
Section: Is There a Role For Compulsory Licenses To Improve Access Tomentioning
confidence: 99%
“…There is also the argument that the price of patented medications is not the main barrier to medication access in LMICs and, in fact, that lack of manufacturing capacity or poor health care systems are larger contributors that impact access. 10 , 15 Counter arguments to this point are simple: if LMICs save money on medication expense, then these savings can be invested in improvement of their own drug manufacturing capacity and health systems. In Thailand, a study found that if relevant HIV/AIDs drugs were not patented, an additional 10,000 prescriptions could be made, which would increase access by 50%.…”
Section: Is There a Role For Compulsory Licenses To Improve Access Tomentioning
confidence: 99%
See 2 more Smart Citations